Groundwater level monitoring using a plastic optical fiber - Esequiel Mesquita (2016)
The present work describes the testing and application of a low cost plastic optical fiber sensor on themonitoring of groundwater levels. Two sensors with different grove depth (œ and Œ ofthe core thickness)and a resolution of 20 cm along 2 m ofthe optical fiber were produced and tested. The sensors were testedunder two experimental setups: water level variation (increasing and decreasing of the water level) andgroundwater increase simulation, in a soil column. The analysis of the optical signal's amplitude and itsvariations due to the increasing or decreasing of water level showed that both tested sensors presentedan appropriate performance and adequate sensibility to groundwater level variation and, therefore, canbe used for in situ applications of monitoring.